Functionalization of mild oxidized graphene with O-phenylenediamine for highly thermally conductive and thermally stable epoxy composites. Issue 102 (21st October 2016) - Akhtar, M. Wasim; Lee, Yun Seon; Yang, Cheol Min; Kim, Jong Seok
Abstract : In this study, an effective and novel method was developed to improve the thermal conductivity of epoxy composites by functionalization of graphene. Abstract : In this study, an effective and novel method was developed to improve the thermal conductivity of epoxy composites by functionalization of graphene. The functionalization of graphene was carried out with a simple refluxing method using a double N-precursor with O -phenylenediamine (OPD), in which the graphene was first treated with acid (2 : 6 molar H2 SO4  : HNO3 ) to form oxygen containing groups on the graphene surface (O-graphene). Amidation and nucleophilic addition reactions through amine groups in OPD contributed significantly to the doping of nitrogen into the graphene layers. The OPD functionalized graphene (OPD-f-graphene) was highly effective and compatible with an epoxy matrix, resulting in homogenous dispersion of a filler in the matrix. The in-plane and through-plane thermal conductivity of the functionalized graphene filled epoxy composite (fG–epoxy) was significantly increased ∼13 fold and ∼4.8 fold, respectively, in comparison to the neat epoxy composite (G–epoxy) with the addition of 6 wt% of the filler. This improvement in thermal conductivity was attributed to better dispersion of the filler into fG–epoxy which generated phonon conduction pathways.